INTRODUCING THE CONCEPT OF AUTONOMOUS AGENTS AS A TOOL TO ASSIST THE ANALYSIS OF THE COLLABORATION BETWEEN MANUFACTURED EXPORTERS AND MARITIME SHIPPERS - Silva, Vanina Macowski Durski; Novaes, Antonio G; Scholz-Reiter, Bernd; Piotrowski, Jakub (International Journal of Industrial Engineering: Theory, Applications and Practice, 2013)
Along export chains transportation has an important cost impacting directly on the efficiency of the whole chain. Experiments show satisfactory results in terms of reduced delivery time, increased productivity of transportation resources as well as economies of scale by the implementation of the Collaborative Transportation Management (CTM). In this context this study intends to present a real Brazilian problem about exports of manufactured products using maritime transportation, as well as introducing the concept of CTM as a tool for helping companies on their decision making. It identifies the major parameters that could support the maritime logistics of manufactured products and, the autonomous agent theory is described as a possible method to solve this logistic problem. As a result for this preliminary study, is intended to awake the readers interest about these emergent concepts applied to such important problem in order to contribute with the costs reduction of the exports chain.